Current Prediction Based Zero Sequence Current Suppression Strategy for the Semicontrolled Open-Winding PMSM Generation System With a Common DC Bus - Zhang, Xiaoguang; Wang, Keqin (IEEE transactions on industrial electronics (1982), 2018)
In this paper, the model predictive current control is introduced in the semicontrolled open-winding permanent magnet synchronous motor (OW-PMSM) generation system with a common dc bus to suppress the zero-sequence current for the first time. Particularly, the basic voltage vectors of the semicontrolled OW-PMSM, which are synthesized by the three-phase full-controlled converter and the three-phase uncontrollable diode bridge, is analyzed and their influences on the zero-sequence current are investigated for the first time in this paper. Then the current-error-based cost function that includes dq-axis current error and zero-sequence current error is designed to evaluate all the voltage vectors. Moreover, to further improve the steady-state control performance of the whole generation system, a zero-sequence current suppression method based on the uncontrollable side voltage vector adjustment, which has the advantage of low computation burden, is developed. In this method, two voltage vectors of the controllable converter are applied during one control period. Based on the distribution character of the basic voltage vector in the semicontrollable OW-PMSM generation system, the first voltage vector is selected according to the three-phase current direction to adjust equivalent vector of the uncontrollable diode bridge, whereas for the second voltage vector, the selection method based deadbeat voltage vector sector is designed to reduce the range of the candidate voltage vector. In addition, the vector durations are also computed. Finally, simulation and experiment are carried out to validate the proposed control approaches.